Vegetative component of function of balance at the sportsmen of different qualifications. - Syshko D.V; Savina K.D; Syshko G.D (Kharkov National Pedagogical University, 2011)
Communication between the type of vestibulevegetative reaction and level of qualification of sportsmen is considered. Were explored hypokinetic, eukinetic and hyperkinetic types of vestibulevegetative reaction at sportsmen with a different level of qualification. Percent correlation of a different level of qualification of sportsmen was determined in every type of vestibulevegetative reaction. In the experiment 87 sportsmen took part the age of 20-25 years old from 2 digits to master of sport of international class. It is set that with growth of sporting trade the percent of sportsmen with the eukinetic type vestibulevegetative of reaction is multiplied, due to reduction of hypo-, and hyperkinetic. The got results enable more exactly to define functional preparedness of sportsmen.